Pembelajaran Kooperatif Tipe Make A Match Dalam Meningkatkan Penguasaan Kosa Kata Bahasa Arab Santri TPA Al-Barokah Hadimulyo Timur Metro Pusat - Muhammad Syaifullah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Developments and changes in social life of nation and state ofIndonesia can not be separated effects of global change, the development ofscience and technology, arts and culture. Changes are constantly demandingthe need for improvement of the national education system, including thecompletion of the curriculum so as to create a society that is able to competeand adjust to the changing times. One of the goals of learning in schools(formal and non-formal) is to improve learning outcomes and in learningthe Arabic language there are four skills that must be learned and masteredby students. The purpose of this research in general is improving resultsvocabulary mastery of Arabic students with a model of cooperative approachto make a match. This study uses classroom action research design. Subjectsin this study is the students of TPA elementary and junior high age children(7-12 years). The data in this study of information about the activities ofteachers and students and the results of beginning test and final test in eachcycle. The results of the application of learning vocabulary with the typecooperative learning methods make a match to mention that, there increasein learning outcomes associated with mastery Arabic vocabulary studentsthe significance of each cycle and also from the initial tests before action.The average class at beginning the pre-action test is 67 increased in the firstcycle 79 and increased again in the second cycle 91. From the test results itcan be seen improvements to the mastery Arabic vocabulary of students ineach cycle.